Aplicação dos princípios da construção enxuta em canteiros de obras suportada por simulação computacional - Araujo, Alexandre Vicentini de (Universidade Federal de São Carlos, 2016)
This research aims to propose and simulate various scenarios based on the principles of Lean Construction aiming to run a reticulated structure of reinforced concrete residential building with multiple floors within the stipulated time in its planning, taking as within seven days (takt time) to completion. The research strategies adopted included a literature review, identification of application opportunities of the principles of Lean Construction, the development of computational model that represented the studied structure, as well as the various scenarios and their simulation. The opportunities of application of the Lean Construction principles were identified through evaluation of Value Stream Mapping (VSM) and Line of Balance (LB). Five scenarios were prepared, the first being the reference, from which were simulated improvements with the use of simulation software ProModel® in 2014. Each version simulation carried out with consideration of an improvement based on the principles of Lean Construction, resulted in the reduction of lead time, converging in the simulation of the latter scenario, for a little higher than the takt time. As a partial indicator of simulation scenarios were evaluated the average cycle times, drive, hold and conversion data they extracted the software used. A comparison of time between the first scenario, depicted as representing the simple observation of the site plus the inherent variability and the latter scenario, characterized by cumulative application of the principles of lean construction, showed that the cycle time returned a reduction in the order of 29% handling increased by 105%, the expected reduced by 54% and the conversion time reduced by 26%. The main result achieved in the fifth scenario was a Lead Time 66.2 hours production. It can be seen that the use of the VSM and simulation provides a clear and concise communication on lean approaches and thus allows the understanding and continuing evolution of Lean concepts.
Keywords: Construção enxuta; Mapa de fluxo de valor; Simulação; Lean construction; Value stream map; Simulation; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL::PROCESSOS CONSTRUTIVOS; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL